PROBLEMS AND PROSPECTS OF DEVELOPMENT OF BANKING INSTITUTIONS IN THE FINANCIAL MARKET OF UKRAINE IN THE CONTEXT OF FINANCIAL SECURITY (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article analyzes the current state of the banking system and banking institutions in Ukraine as the main element of the financial market of Ukraine and highlights the key issues affecting its functioning and strengthening their financial security. It addresses aspects such as regulation, liquidity, credit, innovation, and competitiveness in the context of achieving security goals.Adaptation to a rapidly changing economic landscape, the integration of cutting-edge technologies, and ensuring stability amidst global financial trends emerge as pivotal tasks for the banking sector. Exploring both the problems and prospects becomes imperative in defining the evolving face of Ukraine's banking system within a highly competitive financial environment.The main objective is to determine the peculiarities of the development of banking Ukraine during the war, to single out the main problems and to define a system of measures to solve them.The research reveals the main directions of functioning of the Strategy of the National Bank of Ukraine until 2025. The article examines the causes and consequences of the problems in detail, as well as provides specific recommendations and strategies for overcoming the identified difficulties. In particular, attention is focused on the need to improve legislative regulation, increase the financial stability of banks, develop technological innovations in the banking sector, and strengthen the competitiveness of Ukrainian banks. The article also predicts possible prospects for the development of the banking system of Ukraine in the financial market, taking into account modern trends and challenges.The full-scale invasion of Russia on the territory of Ukraine became a test for the financial system of Ukraine, including the banking system of Ukraine, but it demonstrates high stability and adaptability. That is why today the identification of problems and prospects for the development of the banking sector is an important task for ensuring the efficient functioning of the economy as a whole and to ensure the financial security of banking institutions.
Keywords: banking system, banking institutions, financial market, financial security, banking safety, National Bank of Ukraine, banking innovations.